Study of the Biochemical Method for Wastewater Purification from Textile Productions from Dyes and Suspended Substances - Amonova, Matluba Mukhtarovna (RA Journal of Applied Research, 2022)
Wastewater treatment in textile production is a multi-stage process that requires correct step-by-step processing, since textile auxiliary substances can be toxic. In this regard, this article discusses the combined, i.e. sorption-coagulation-flocculation treatment of waste water from textile production. The use of a combined cleaning method contributes to a more complete removal of surfactants, inorganic and organic substances, dyes, suspended solids and various salts. The effective conditions for the sorption of the dye from an aqueous solution selected by the sorbent have been determined. It was found that the effective mass of the sorbent is within 0.2; 0.3; 0.4; 0.5; 0.6 g per 100 ml of solution. It was found that an increase in mass significantly increases the purification of the solution from the dye, and leads to a decrease in the optical density at the points corresponding to 0.4 and 0.6 g. It has been determined that the initial values of the main indicators of wastewater entering the deep purification at a bubbling adsorption unit correspond to the values ​​of the indicators of these flows passing through a system consisting of kaolin-bentonite-aluminum sulfate-ferric chloride. Since the main indicators of pollution are the intensity of coloring and surfactants for wastewater from textile and silk-winding factories, studies on the effect of the size of adsorbent particles and speed on the adsorption process were primarily carried out for these indicators. At the same time, it was determined that the maximum (up to 97%) wastewater treatment from surfactants and dyes by a chemical method when using the composition K-5 and K-6 is achieved with a particle size of sorbents of 0.5-0.6 nm.